2010
DOI: 10.1007/s10549-010-1122-6
|View full text |Cite
|
Sign up to set email alerts
|

Transient over-expression of estrogen receptor-α in breast cancer cells promotes cell survival and estrogen-independent growth

Abstract: shows that the apoptosis gene set differentially expressed in MLET5 is enriched for estrogen-regulated genes, our findings suggest that transient over-expression of ERα could lead to increased cell survival and the development of estrogenindependent growth, thereby contributing to resistance to endocrine therapies in breast cancer patients.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…With genomic and nongenomic actions affecting proliferation, migration, and apoptosis, the ERa has a central role in the biology of breast cancer. Indeed, prior studies have demonstrated that the ERa can protect breast cancer cells from program-induced cell death, in part, by modulating the expression of apoptosisrelated genes, such as BCL2, BIK, and BMF (16,38,39). Whereas very few of the well-established ERa-target genes (i.e., GREB1, TFF1, CCND1, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With genomic and nongenomic actions affecting proliferation, migration, and apoptosis, the ERa has a central role in the biology of breast cancer. Indeed, prior studies have demonstrated that the ERa can protect breast cancer cells from program-induced cell death, in part, by modulating the expression of apoptosisrelated genes, such as BCL2, BIK, and BMF (16,38,39). Whereas very few of the well-established ERa-target genes (i.e., GREB1, TFF1, CCND1, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Genes whose transcript levels were increased by emetine treatment potentially contained a nonsense mutation and were prioritized on the basis of those that aligned to regions of LOH or deletion as assayed by genotyping with singlenucleotide polymorphisms (SNP) arrays. Using this strategy, we identified and further established the AT-rich interactive domain 1a (ARID1A) as a candidate tumor-suppressor gene in breast cancer, a finding that has since been confirmed by the discovery of ARID1A mutations in breast tumors by several groups (16,18). Similarly, we identified an insertion/truncation mutation at nucleotide 1184 in the SPEN gene and LOH at the SPEN locus (chromosome 1p36), resulting in undetectable SPEN protein levels in the ERa-positive, T47D breast cancer cell line (Supplementary Fig.…”
Section: Spen Is Mutated and Underexpressed In Breast Tumorsmentioning
confidence: 95%
“…The breast cancer cell lines CAL51 (German Resource Centre for Biological Material, DSMz, Braunschweig, Germany) and MCF7 (European Collection of Cell Cultures, Health Protection Agency, UK) were grown in low glucose (1 g/l) Dulbecco's modified Eagle's medium (DMEM)-GlutaMax (Invitrogen, Carlsbad, CA, USA) supplemented with 10% foetal calf serum (FCS). Drug-resistant derivatives CALDOX, MCFDOX and MLET5 have been previously described (16)(17)(18). RNA from MDA-MB-231, T47D, zR75 and 226-L-U19 cells (19) was a generous gift from Y. zhou.…”
Section: Methodsmentioning
confidence: 99%
“…Then we examined whether TRIAP1 was associated with a drugresistance phenotype. For this, we tested TRIAP1 mRNA expression in two doxorubicin-resistant breast cancer cell lines derived from CAL51 (16) and MCF7 (17) cells, and in a third cell line derived from MCF7 cells after estrogen deprivation, which are resistant to tamoxifen and etoposide (18). Doxorubicin and etoposide are two topoisomerase II inhibitors producing genotoxic stress, ultimately leading to apoptosis, which form part of many chemotherapeutic cancer regimes.…”
Section: Triap1 Is Ubiquitously Expressed In Normal Human Tissues Andmentioning
confidence: 99%
“…The role of ERα in breast cancer development has been extensively investigated. Transient over-expression of ERα promotes cell survival and estrogen-independent growth [6] whereas ERα knock-down induces cell apoptosis and growth inhibition [7] in estrogen-responsive MCF-7 breast cancer cells. Recent research also indicates that estrogen-independent ERα signaling and its interaction with growth factor receptors contribute to endocrine resistance in breast cancer treatment [8].…”
Section: Introductionmentioning
confidence: 99%